2009
DOI: 10.1111/j.1744-697x.2009.00130.x
|View full text |Cite
|
Sign up to set email alerts
|

Cultivation and ensilage of yacon plants (Smallanthus sonchifolius [Poepp. & Endl.] H. Robinson) and the function of yacon silage

Abstract: Yacon (Smallanthus sonchifolius [Poepp. & Endl.] H. Robinson) plant cultivation has extended rapidly throughout Japan since 1985 because of its utility as a tuberous root crop. In this study, strains with high yields of both above‐ground and underground parts were identified to investigate the use of above‐ground parts for animal feed silage. In addition, we measured the anti‐oxidative activity of the silage as a functional characteristic. Data from 5 years of the cultivation of 17 yacon strains suggest that t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
11
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(15 citation statements)
references
References 7 publications
(17 reference statements)
3
11
0
Order By: Relevance
“…However, a large amount of the foliage parts of yacon are hardly used. Therefore, we suggest that the entire yacon plant is used as a feed resource by ensiling, as discussed in the previously published report (Koike et al 2009).…”
Section: Introductionmentioning
confidence: 59%
See 4 more Smart Citations
“…However, a large amount of the foliage parts of yacon are hardly used. Therefore, we suggest that the entire yacon plant is used as a feed resource by ensiling, as discussed in the previously published report (Koike et al 2009).…”
Section: Introductionmentioning
confidence: 59%
“…In conclusion, it is suggested that YS can be used not only as feed for monogastric animals (Koike et al. 2009), but also as a supplementary feed in ruminants.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations